2013
DOI: 10.5350/semb2013470103
|View full text |Cite
|
Sign up to set email alerts
|

Yoğun bakım ünitemizdeki (YBÜ) perkütan trakeotomi pratiğimiz

Abstract: P apillary thyroid carcinoma (PTC) is the most common endocrine malignancy. [1] The incidence of papillary thyroid cancer is increasing tremendously in developed countries, mostly because of the determination of intrathyroidal papillary microcarcinomas that has led to suspects regarding overdiagnosis and overtreatment. [2][3][4] The incidence of thyroid carcinoma increased by three-fold between 1975 and 2009 in the US and was reported to be 15 times greater in 2011 than in 1993, which is mainly due to the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
2
6
0
2
Order By: Relevance
“…PT has numerous advantages such as requiring small skin incision, causing less tissue damage, bleeding, and stoma infection, and easy bedside application (7,10,11). For these reasons, PT is more popular than surgical tracheostomy (7,10). However, a study conducted in Turkey evaluated ICU patients for a period of three years and reported that out of the 203 patients that underwent tracheostomy during the study period, 99 (48.8%) of them underwent PT and the remaining 104 (51.2%) patients underwent surgical tracheostomy (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PT has numerous advantages such as requiring small skin incision, causing less tissue damage, bleeding, and stoma infection, and easy bedside application (7,10,11). For these reasons, PT is more popular than surgical tracheostomy (7,10). However, a study conducted in Turkey evaluated ICU patients for a period of three years and reported that out of the 203 patients that underwent tracheostomy during the study period, 99 (48.8%) of them underwent PT and the remaining 104 (51.2%) patients underwent surgical tracheostomy (1).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous tracheostomy (PT) has been shown to be a viable method due to its key advantages including easy bedside application, low complication rates, and short application time. Moreover, PT is frequently used in ICU patients requiring elective tracheostomy (6,7). As PT is an invasive procedure, it may lead to both intra-and post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…PT'nin avantajları; küçük bir deri insizyonu ile yapılması, dokuda daha az hasarlanma yapması, kanamada azalma, stoma enfeksiyonunda azalma, trakeal problemlerde azalma, kozmetik deformitede azalma, yatak başı yapılabilmesi, ameliyathane gereksinimi olmadığı için transport riski ve masrafında azalma, kısa sürede açılabilmesi, komplikasyon oranlarında azalma ve cerrahi eğitimi olmayan doktorlar tarafından da açılabilmesidir (5,7,9,10). Bu nedenlerden dolayı PT cerrahi trakeostomiye oranla daha çok tercih edilmektedir (7,9). Bizim YB'de son 2 yılda yatan 276 hastanın 31'ine cerrahi trakeostomi, 132'sine PT açıldı.…”
Section: Gereç Ve Yöntemunclassified
“…Genel olarak cerrahi trakeostomi uygulamaları daha çok kulak burun boğaz ve göğüs cerrahisi uzmanlarınca uygulanırken, perkütan trakeostomi (PT) uygulamaları daha çok kulak burun boğaz, anesteziyoloji ve reanimasyon ve YB uzmanları tarafından uygulanabilmektedir (3,4). Günümüzde birçok PT yöntemi tarif edilmiş olmasına rağmen en sık kullanılan teknikler PT'nin kolay uygulanabilirliği, düşük komplikasyon oranları ve hasta yatağında kısa sürede uygulanabilen bir yöntem olduğu için son yıllarda daha çok tercih edildiği ve özellikle elektif trakeostomi açılacak olgularda YB ünitesinde sıklıkla kullanıldığı görülmektedir (4,7). PT işlemi sırasında; kanama, hipoksi, hiperkapni, pnömotoraks, pnömomediastinum, deri altı amfizem, paratrakeal yerleşim, trakea duvar yaralanması, aspirasyon, ani ölüm, özofagus hasarı gibi komplikasyonlar görülebilmektedir (4,8).…”
Section: Introductionunclassified
“…Tracheostomy is a surgical method frequently applied to patients with long term mechanical ventilation, for treatment of upper respiratory tract obstruction, and those with endotracheal intubation in ICU and predicted to remain linked to a mechanical ventilator for a long period (27,28). Percutaneous tracheostomy (PT) is easily performed, has low complication rates and can be performed in a short period at the patient's bedside so it is mostly chosen in recent years and is frequently used in the ICU for cases with elective tracheostomy especially (29,30). During the PT procedure, complications like hemorrhage, hypoxia, hypercapnia, pneumothorax, pneumomediastinum, subdermal emphysema, paratracheal insertion, tracheal wall injury, aspiration, sudden death, and esophagus injury may be observed (29).…”
Section: Discussionmentioning
confidence: 99%